Acupuncture Versus Biofeedback for Treatment of Functional Anorectal Pain - Xue, Yahong; Ding, Shuqing; Zhou, Huifen; Li, Min; Cao, Jianbao; Chen, Qian; Ding, Yijiang (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Functional anorectal pain is one of several types of functional anorectal disorders. In this study, we compared the effectiveness of acupuncture (intervention) and biofeedback (control) as treatment for patients with functional anorectal pain. Materials and Methods: This prospective, single-center, randomized, and comparative study examined 68 patients with functional anorectal pain who were recruited from June 2017 to January 2019 at the Nanjing Hospital of Chinese Medicine Affiliated to Nanjing University of Chinese Medicine. Patients were randomly assigned to receive acupuncture or biofeedback. Patients in the acupuncture group received acupuncture at Zhongliao (BL33), Xialiao (BL34), Ganshu (BL18), Shenshu (BL23), and Dachangshu (BL25). Patients in the biofeedback group received pelvic floor biofeedback therapy, consisting of Kegel pelvic floor muscle training and electrical stimulation. Patients in both groups received 20 treatments over 4 weeks. The primary outcome was pain score on a visual analog scale, and the secondary outcomes were results from the MOS 36-item short-form health survey (SF-36) quality of life questionnaire, the self-rating depression scale, and the self-rating anxiety scale. Results: Visual analog scale pain scores significantly decreased in both of the groups with treatment (both P < .01). The final visual analog scale score was significantly lower in patients with pelvic floor dyssynergia who were treated with biofeedback (1.40 ± 0.97 vs. 5.30 ± 1.70) (P < .05). The 2 groups had similar decreases in self-rating depression scale and self-rating anxiety scale scores. Intriguingly, the acupuncture group had better mental health outcomes (P < .05). Conclusion: Both acupuncture and biofeedback therapy reduced the pain of patients with functional anorectal pain. Biofeedback provided more relief in patients with pelvic floor dyssynergia, and acupuncture provided greater improvements in mental health status. Cite this article as: Xue Y, Ding S, Zhou H, et al. Acupuncture versus biofeedback for treatment of functional anorectal pain. Turk J Gastroenterol. 2024;35(2):83-91.